PENYULUHAN PENGEMBANGAN KARAKTER DAN KETERAMPILAN PADA ANGGOTA KARANG TARUNA CIPINANG BESAR UTARA - Pratama, Bayu; Novyarni, Nelli; Mulya, Abidah Ardelia; Ikhsana, Julita Yasmien; Sabillah, Niken (MAJU : Indonesian Journal of Community Empowerment, 2024)
This article discusses character and skill development counselling for members of Karang Taruna RW 08 Cipinang Besar Utara through a structured extension program. The method used is a participatory approach that involves members of Karang Taruna in every stage of the activity. Counselling activities include practical skills training and discussions about character values, such as leadership, cooperation, and social responsibility. The evaluation results showed significant improvements in member skills as well as positive changes in attitudes and behaviours. Thus, this program not only contributes to individual development, but also strengthens the role of Karang Taruna as a change agent in the community. This PKM activity is an effort to equip the members of Karang Taruna RW 08 Cipinang Besar Utara with the necessary provisions to become a superior young generation. Through this counselling, the cadet members are expected to be able to develop strong characters and skills that are relevant to the needs of the working world. It is hoped that, with the provisions they have, the participants can become agents of change in their environment and contribute to community development.